Small ruminants in a High Nature Cultural Value agroforestry system. Case studies in sheep research - Gaspar P.; Elghannam A.; Escribano M.; Mesías F.J. (Innovation for sustainability in sheep and goats, 2019)
Sheep and goat systems in south west Spain are “suffering” the same as any other extensive ruminant systems the Mediterranean area. Specifically, sheep farms have been endangered in recent years due to various pressures derived from changes in the consumption patterns and public policy changes. These systems are extremely fragile, as well as having a key role in providing environmental services. In this paper two case studies are presented. The first one is dealing with dairy herds of Merino ewes producing under a PDO scheme. In this case we analyse the farmers’ perception of their relationship with the PDO “Torta del Casar”, one of the most well-known Cheese PDOs in Spain, focusing on the technical and economic benefits that they obtain from their membership. The second case is related to sheep for meat systems. A sample of 101 sheep farms belonging to a second degree cooperative has been analysed. From this case we can conclude that the integration of farms into cooperatives can improve farm structure and ensure their persistence, due to the provision of additional services to the farmer, the generation of added value and increased price stability. Both cases are examples of successful strategies to improve the level of competitiveness of the productive system and the viability of the farms.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)